DENTOFACIAL IMPLICATIONS OF RICKETS: INSIGHTS FROM PEDIATRIC CASES (World Bulletin of Public Health, 2024)
This research focuses on the dental manifestations of rickets, a vitamin D-resistant disease that affects the mineralization of hard tissues in both primary and permanent dentition. The study investigates various clinical, morphofunctional, anthropometric, radiological, and histopathological aspects related to dental complications in children during the primary occlusion period. Utilizing diverse research methods such as clinical examinations, anthropometric measurements, X-rays, photometry, laboratory analyses, and statistical data processing, the research delves into the impact of vitamin D deficiency on calcium and phosphate absorption. The findings highlight distinct dental features associated with X-linked hypophosphatemia, a form of vitamin D-resistant rickets, including enlarged pulp chambers, enamel and dentin defects, and alterations in lamina dura. Histological analysis underscores dentin's vulnerability, showing pronounced globular dentin and widened predentin, while enamel remains thinner but typically normal. The study emphasizes the complications in primary dentition, such as tooth loss leading to dental arch deformation, colour changes in the central incisor, and clinically and radiologically diagnosed caries in primary molars.
Keywords: Rickets; Vitamin D-resistant disease; Dental complications